Driving Factors and Effectiveness of Sales Promotion in Shopping Malls: A Consumer Perspective - Chavadi, Chandan A.; Kokatnur, Shilpa S. (Indian Journal of Marketing, 2010)
With the emergence of big players such as Bharati, Reliance, Future group and others, the retail sector is facing stiff competition, both in terms of product and service mix. Increasing disposable incomes, rising consumer expectations and enhanced shopping experience has thrown a lot of opportunities and challenges for the retailers. Each and every organized retailer is under threshold pressure to offer their best to customers. Right from the procurement of merchandise to the delivery of products, ways and means have been tried out by retailers to add value in each and every phase. Retailers may carry the best product mix, but they may not be able to reach the possible sales levels if promotions are not conceptualized and implemented aggressively. Where advertisement offers a reason to buy, sales promotion offer an incentive to buy. It can be understood from the past that advertisement to sales promotion ratio is undergoing prodigious change from 60 to 40% to 75 to 65% of the combined budget. Last two decades have witnessed increased percentage of budget expenditure on sales promotion by the companies. Earlier, sales promotion was ethically questioned and companies refrained from doing so. But now, it has become professional and marketers increasingly plan sales promotions first and ads later. According to an Economic Times report (June 15, 2003), the sales promotion activities by the Indian industries have increased by 500 to 600 percent in the last 3 to 5 years.